2016
DOI: 10.1111/jnc.13578
|View full text |Cite
|
Sign up to set email alerts
|

Direct interaction of the resistance to inhibitors of cholinesterase type 3 protein with the serotonin receptor type 3A intracellular domain

Abstract: Pentameric ligand-gated ion channels (pLGIC) are expressed in both excitable and non-excitable cells that are targeted by numerous clinically used drugs. Assembly from five identical or homologous subunits yields homo- or heteromeric pentamers, respectively. The protein known as Resistance to Inhibitors of Cholinesterase (RIC-3) was identified to interfere with assembly and functional maturation of pLGICs. We have shown previously for serotonin type 3A homopentamers (5-HT3A) that the interaction with RIC-3 req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 55 publications
(139 reference statements)
0
35
0
Order By: Relevance
“…In summary, from previous studies, it is known that the 5-HT 3A -ICD is required and sufficient for interaction of the 5-HT 3A R and RIC-3. Furthermore, this direct interaction between the ICD and RIC-3 does not require the presence of other host cell proteins [21][22][23][24][25]. In the current study, we aimed to identify the segment of the ICD responsible for this interaction with the hypothesis that the interaction site lies within an independent segment of the ICD.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In summary, from previous studies, it is known that the 5-HT 3A -ICD is required and sufficient for interaction of the 5-HT 3A R and RIC-3. Furthermore, this direct interaction between the ICD and RIC-3 does not require the presence of other host cell proteins [21][22][23][24][25]. In the current study, we aimed to identify the segment of the ICD responsible for this interaction with the hypothesis that the interaction site lies within an independent segment of the ICD.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we demonstrated that the interaction between GLIC-5-HT 3A -ICD and RIC-3 is direct and does not require the presence of additional proteins. Both proteins were overexpressed in and purified from Escherichia coli (E. coli) and were subjected to a pull-down assay through which we observed an interaction between the two proteins [24]. Subsequently, in a separate study we examined if the 5-HT 3A -ICD alone is sufficient to retain an interaction with RIC-3.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ICD is involved in determining ion conductance (23, 35) and modulation by drugs (36). Additionally, it interacts with various entities of the intracellular apparatus, which facilitate receptor sorting, assembly, trafficking, and anchorage (37, 38). Studies of subunit assembly and oligomerization have investigated the individual contributions of ECD (39, 40) as well as TMD (30, 31) at the molecular level.…”
Section: Introductionmentioning
confidence: 99%